Language Teaching Research and Language Pedagogy - Ellis, Rod.; Wiley InterScience (Online service) (Malden, MA : John Wiley & Sons Inc., 2012)
This book examines current research centered on the second language classroom and the implications of this research for both the teaching and learning of foreign languages. It offers illuminating insights into the important relationship between research and teaching, and the inherent complexities of the teaching and learning of foreign languages in classroom settings.
Introduction: Developments in Language Teaching Research -- Methods for Researching the Second Language Classroom -- Comparative Method Studies -- Second Language Classroom Discourse -- Focus on the Teacher -- Focus on the Learner -- Investigating the Performance of Tasks -- Interaction and L2 Learning in the Classroom -- Form-Focused Instruction and Second Language Learning -- Instruction, Individual Differences and L2 Learning -- Conclusion: Research and Language Teaching.
Includes bibliographical references and index.
Print version record.
Keywords: Language and languages -- Study and teaching; Language and languages -- Research; Language teachers -- Training of; Language and languages -- Research; Language and languages -- Study and teaching; Language teachers -- Training of; Electronic books